The Effect of Antioxidants on Egg Quality and Laying Hen Productivity - Osama Abdael Salam Ambia Amoush (Bani Waleed University Journal of Humanities and Applied Sciences, 2025)
This study aims to evaluate the effects of different antioxidants, including selenium, vitamin E, and polyphenolic compounds, on egg quality and laying hen productivity. The study was conducted on different groups of laying hens, where antioxidants were added to the feed in specified doses. The results showed significant improvements in eggshell thickness and strength, a reduction in lipid oxidation levels in the egg yolk, and an enhancement in yolk color intensity. Additionally, egg production rates and feed conversion efficiency were positively influenced. Statistical analyses revealed significant differences among the experimental groups, indicating the high effectiveness of antioxidants in improving egg quality. The study recommends the incorporation of antioxidants in poultry feeding programs to enhance productivity and quality.